AN OVERVIEW OF THE LEVEL OF IMPOSTOR PHENOMENON AMONG PROFESSIONAL NURSING STUDENTS AT THE FACULTY OF NURSING, UNIVERSITAS PADJADJARAN - Argalita Restu Wigasantri; Taty Hernawaty; Setiawan Setiawan (Universitas Airlangga, 2026)
Introduction: The Impostor Phenomenon (IP) is a psychological condition in which individuals doubt their abilities and fear being exposed as frauds despite their achievements. This study aims to describe the level of IP among professional nursing students at Universitas Padjadjaran. Methods: This quantitative descriptive study used a cross-sectional approach. The population consisted of 142 professional nursing students from the Jatinangor and Pangandaran campuses. Data were collected from 108 respondents (response rate: 76%) selected through a total sampling technique. The Clance Impostor Phenomenon Scale (CIPS) was used to measure impostor feelings. This instrument consists of 20 items using a 5-point Likert scale (total score range: 20–100). The CIPS has been previously validated in the Indonesian context with a high reliability coefficient (Cronbach’s alpha = 0.87). Data were analyzed using univariate analysis to determine the frequency distribution and percentages of impostor levels. Results: The findings showed that the majority of respondents (59.3%) experienced a high level of Impostor Phenomenon, with an average score of 62.43. In terms of specific indicators, perfectionism had the highest average score of 3.28 (65.7%), followed by self-doubt at 3.26 (65.3%), both falling into the high category. Conversely, the social comparison indicator showed the lowest level (average score = 2.76 or 55.3%). Conclusions: Most professional nursing students experience high levels of IP, indicating a discrepancy between their actual competence and self-perception. Educational institutions should implement structured psychological support, such as mentoring and peer-support groups, to enhance students' professional confidence and clinical readiness.